2021
DOI: 10.1080/26884674.2021.1921634
|View full text |Cite
|
Sign up to set email alerts
|

Greensplaining environmental justice: A narrative of race, ethnicity, and justice in urban greenspace development

Abstract: While urban greenspaces play an important role in shaping the cultural and social dimensions of cities, these spaces are also inherently political, often serving to perpetuate the exclusion and subordination of racially marginalized populations. Drawing upon critical race theory, the purpose of this research is to use narratives to highlight how race, structural racism, White privilege, and power continue to shape environmental injustices in the urban landscape. By sharing these stories, we illustrate how (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…While studies have shown that community greening efforts in lower income and minority neighborhoods do not automatically promote health equity [18], they are nonetheless connected to other social factors such as community revitalization, affordable housing, neighborhood walkability, food security, job creation, and youth engagement [22]. Urban green spaces contribute to the cultural and social dimensions of cities, but they are also inherently political; the trend of "greensplaining" can be used as further justification for White privilege, racialized marginalization, and processes of gentrification [23].…”
Section: Introductionmentioning
confidence: 99%
“…While studies have shown that community greening efforts in lower income and minority neighborhoods do not automatically promote health equity [18], they are nonetheless connected to other social factors such as community revitalization, affordable housing, neighborhood walkability, food security, job creation, and youth engagement [22]. Urban green spaces contribute to the cultural and social dimensions of cities, but they are also inherently political; the trend of "greensplaining" can be used as further justification for White privilege, racialized marginalization, and processes of gentrification [23].…”
Section: Introductionmentioning
confidence: 99%